999Impact of Heatwaves on use of health services (GP and Emergency department visits). (2nd September 2021) - Varghese, Blesson; Beaty, Matt; Bi, Peng; Nairn, John
Abstract: Background: Heatwaves are associated with increases in mortality and morbidity (mostly hospitalisations). However, evidence regarding heatwave impacts on the use of frontline health-services such as general practitioner (GP) consultations and emergency department (ED) services is limited. This study quantified the impact of heatwaves on the use of GP and ED services in Adelaide. Methods: Data on GP services (2011-2016) from the Medicare Benefits Schedule and ED visits (2013-2018) were obtained from the Australian Bureau of Statistics and the Department of Health, respectively. Heatwaves were defined using Excess Heat Factor. Using time-stratified case-crossover models, we modelled heatwave-severity (low, severe/extreme) against the use of GP and ED services in the warm-season (October-March). Effect estimates are reported as relative risks (RRs). Results: Total GP visits decreased during low-intensity heatwaves and increased during severe/extreme heatwaves (RR 1.14; 95%CI: 1.13-1.15). The highest increases during severe/extreme heatwaves were observed for respiratory (RR 1.36; 95%CI: 1.27-1.45) and psychiatric services. While ED visits decreased overall during low-intensity and severe/extreme heatwaves, those due to heat-light disorders (RR 4.23; 95%CI: 2.98-6.00), volume depletion, and respiratory diseases increased during severe/extreme heatwaves. Conclusions: There were significant increases in the use of GP and specific ED services during heatwaves in Adelaide. Further research is needed to identify the intrinsic and extrinsic vulnerability factors contributing to these increases in Adelaide and other Australian cities. Key messages: Impacts of heatwaves extend beyond mortality to include frontline health-services (GP/EDs) that are already challenged. Evidence presented may assist policymakers for resource allocation and healthcare workforce capacity building.